ANALISIS EFISIENSI SALURAN DAN EFEKTIVITAS DAERAH IRIGASI OONGAN PADA DAERAH ALIRAN SUNGAI (DAS) TUKAD AYUNG - KRISNA KURNIARI; I MADE NADA; I GEDE SUADNYANA (Universitas Mahasaraswati K. Mataram, 2023)
The Oongan Irrigation Area, which is located in East Denpasar as part of the Tukad Ayung River Basin, has a potential land area of 1781 Ha, but only 617 Ha has been utilized. In March 2019, the average discharge reached 680 l/second, while the Oongan intake gate required a discharge of 880.7 l/s for the rice growing period. Based on these data, there is a need for in-depth research in the Oongan Irrigation Area regarding the efficiency and effectiveness of irrigation canals.. The research method used is the survey method. Based on the results of the analysis of the efficiency of the primary and secondary canals and the effectiveness of the Oongan Irrigation Area, the percentage results were 80.47%, 94.1% and 35% which showed that the primary canal was not efficient and irrigation that was not effective was below the standard value, namely 90% and 55%. There needs to be an improvement both in the water management system and the physical improvement of irrigation infrastructure. Meanwhile, secondary canals get an average yield with a percentage of 94.1% which is included in the efficient category so that it needs to be maintained and carried out maintenance through operational and maintenance activities on irrigation canals.